INTERAKSI ANAK TUNAGRAHITA PADA KEHIDUPAN BERMASYARAKAT DI KAMPUNG TRIKOLOT PANDEGLANG - Said; Yahdinil Firda Nadhirah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research aims to deeply describe the forms of social interaction of children with intellectual disabilities in community life in Kampung Tarikolot, as well as to identify the factors that support and hinder this social interaction process. The research focus is directed toward how children with intellectual disabilities interact with their social environment, how society responds to their presence, and the roles of family and school in supporting their social development. This research uses a qualitative approach with a case study method, as it is considered capable of exploring social phenomena in depth and contextually. Data collection techniques were carried out thru direct observation of children's social behavior and in-depth interviews with parents as the primary informants. The research findings indicate that children with intellectual disabilities have a fairly good level of social interest and demonstrate a desire to engage in social interaction within the community. However, the child still experiences limitations in initiating interactions, maintaining communication, and fully understanding social rules and dynamics. The social interactions they engage in tend to be simple and responsive, rather than self-initiated. Family support, especially the role of parents, is a key factor in helping children adjust socially. Additionally, a school environment that implements the principles of inclusive education also contributes positively to the development of children's social skills. Conversely, social stigma, the passive attitudes of a segment of society, and a lack of understanding regarding intellectual disabilities pose significant obstacles. Therefore, this research underscores the importance of collaboration between families, schools, and communities in creating an inclusive, supportive, and humanistic social environment to support the social development and quality of life of children with intellectual disabilities.